158k views
11 votes
Solve 2x²+x-4 = 0.
²+1/2
1
2
x² +
23
x + -2
x + 2

1 Answer

6 votes

Answer:


x = (-1 \pm √(33))/(4)

Explanation:

Hello!

We can solve the quadratic by using the Quadratic Formula.

Standard form of a Quadratic:
ax^2 + bx +c = 0

Quadratic Formula:
x = (-b \pm √(b^2 - 4ac))/(2a)

Given our equation:
2x^2 + x - 4 = 0

  • a = 2
  • b = 1
  • c = -4

Plug in the values into the quadratic formula to solve.

Solve the quadratic


  • x = (-b \pm √(b^2 - 4ac))/(2a)

  • x = (-1 \pm √(1^2 - 4(2)(-4)))/(2(2))

  • x = (-1 \pm √(1 + 32))/(4)

  • x = (-1 \pm √(33))/(4)

The solution to the quadratic is
x = (-1 \pm √(33))/(4).

User Igor Zelmanovich
by
5.2k points